2020
DOI: 10.5194/gc-2020-45
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Flexible, Open and Interactive Digital Platform to Support Online and Blended Experiential Learning Environments: Thinglink and thin sections

Abstract: Abstract. This study investigates the potential value of, and provides a method for the creation of, flexible, digital and asynchronous platforms to create student-centered materials for use in an online and/or blended learning environment. We made use of Thinglink to create a virtual microscope resource for geology and associated courses in higher education. This is achieved through the dissemination of a simple learning resource comprising interactive imagery and audio. The visual analysis of rocks under the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The incorporation of observations at multiple scales is another important aspect highlighted in previous work [41]. Indeed, a multi-scale approach is a central aspect in some previous VFTs [41] and some work focuses on the development of virtual microscope environments [42]. In fact, multiscale observations are potentially more possible in VFTs than regular in-person fieldwork because it allows the students to focus on pertinent details without being overwhelmed by the larger scale processes, geometries and other aspects.…”
Section: Data Types Materials and Resourcesmentioning
confidence: 99%
“…The incorporation of observations at multiple scales is another important aspect highlighted in previous work [41]. Indeed, a multi-scale approach is a central aspect in some previous VFTs [41] and some work focuses on the development of virtual microscope environments [42]. In fact, multiscale observations are potentially more possible in VFTs than regular in-person fieldwork because it allows the students to focus on pertinent details without being overwhelmed by the larger scale processes, geometries and other aspects.…”
Section: Data Types Materials and Resourcesmentioning
confidence: 99%
“…The actual nature of a virtualised laboratory can range considerably in scale and scope, from compact and simple materials designed to meet very specific learning outcomes such as those found in an individual class (e.g. Jeffery et al, 2021) to materials designed in full 3 -D environments and/or covering a considerable range of academic material (e.g. Hernández-de-Menéndez et al, 2019 and references therein).…”
Section: ) Embedding Campus As a Classroom/livingmentioning
confidence: 99%
“…Under the Equality Act 2010 (Legislation.gov.uk, 2010), educators are obliged to provide reasonable adjustments and ensure that materials are accessible for learners with additional needs. To this end, we have found that the application of asynchronous virtualised forms of the instruments given above has been viewed as favourable to learning by learner and educator alike, by providin g learners with a means of exploring an instrument or technique at a time and place of their choosing, in an interactive and accessible form (Jeffery et al, 2021). These resources therefore have the potential to provide a powerful complement to Living Labs, adding depth, diversity, and flexibility, particularly when treated in a supplementary fashion (e.g.…”
Section: ) Embedding Campus As a Classroom/livingmentioning
confidence: 99%